Enhancing the Statutory Roles of the Shariah Advisory Council of Bank Negara Malaysia through Technological Advancement: A Way Forward - Izzat Amsyar Mohd Arif, Mohd; Markom, Ruzian; Adenan, Faezy; Saifuddin, Suhaizad (KnE Social Sciences, 2024)
The Central Bank Act of 2009 established the Shariah Advisory Council of Bank Negara Malaysia as the exclusive and highest authority responsible for issuing resolutions on Shariah matters pertaining to Islamic finance. An in-depth analysis of the Shariah Advisory Council’s legal standing is provided in this article. The Shariah Advisory Council’s legal obligations will also be clarified. To determine where the Shariah Advisory Council fits within the context of Malaysian law, quantitative analysis of content is employed with reference to parliamentary acts, directives, as well as judicial rulings through court cases. The investigation discovered that the use of digital technologies can strengthen the Shariah Advisory Council’s mandated duties. As a result, it is suggested that internal policies and processes, plans for empowering Shariah resolutions, and public reference bodies be established. Keywords: Islamic finance, Shariah advisory council, Shariah authority